Socioeconomic determinants of health enhancing expenditure among the elderly in Malaysia: an ethnic comparison - Yong, Kang Cheah (Penerbit Universiti Kebangsaan Malaysia, 2015)
The objective of this study is to examine the effects of socioeconomic factors on consumption of health-enhancing goods and services among different ethnicities of the elderly in Malaysia. The Third National Health and Morbidity Survey (NHMS III) comprising 4573 respondents (aged ≥ 60) is used for analysis. The results suggest that age, income, gender, education and location of residence are significantly associated with consumption of health-enhancing goods and services. Specifically, there are negative relationships between the likelihood of consuming health-enhancing goods and services and older individuals, lower income earners, males, the less-educated, and rural dwellers. Based on these findings, several intervention strategies toward promoting the consumption of health-enhancing goods and services are suggested.